Nitric oxide increases the enzymatic activity of three ascorbate peroxidase isoforms in soybean root nodules - Keyster, Marshall (Landes Bioscience, 2011)
Ascorbate peroxidase is one of the major enzymes regulating the levels of H(2)O(2) in plants and plays a crucial role in maintaining root nodule redox status. We used fully developed and mature nitrogen fixing root nodules from soybean plants to analyze the effect of exogenously applied nitric oxide, generated from the nitric oxide donor 2,2′-(hydroxynitrosohydrazono)bis-ethanimine, on the enzymatic activity of soybean root nodule ascorbate peroxidase. Nitric oxide caused an increase in the total enzymatic activity of ascorbate peroxidase. The nitric oxide-induced changes in ascorbate peroxidase enzymatic activity were coupled to altered nodule H(2)O(2) content. Further analysis of ascorbate peroxidase enzymatic activity identified three ascorbate peroxidase isoforms for which augmented enzymatic activity occurred in response to nitric oxide. Our results demonstrate that nitric oxide regulates soybean root nodule ascorbate peroxidase activity. We propose a role of nitric oxide in regulating ascorbate-dependent redox status in soybean root nodule tissue.